1976
DOI: 10.1159/000130668
|View full text |Cite
|
Sign up to set email alerts
|

Chiasmata, meiotic univalents, and age in relation to aneuploid imbalance in mice

Abstract: Chiasmata were counted and paired and unpaired configurations at first meiotic division and chromosome errors at second meiotic division were assessed at different ages in males and females of two strains of laboratory mice. In the females a decrease of chiasma frequency and an increase of univalents at first meiotic metaphase (MI) were confirmed. In the males, diakineses had higher chiasma frequencies (in the range of the female Mis) and fewer univalents than the MIs had. In these male cells there was no decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 4 publications
5
42
1
Order By: Relevance
“…In CD1 and in Mil II mice, the mean number of MLH1 foci did not change from 3-to 7-month-old animals in agreement with the long-recognized fact that recombination frequencies do not change with age in male mice (Polani and Jagiello, 1976;Jagiello and Fang, 1979). Instead, a significant reduction in the mean number of MLH1 foci was found in 5-month-old heterozygous mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In CD1 and in Mil II mice, the mean number of MLH1 foci did not change from 3-to 7-month-old animals in agreement with the long-recognized fact that recombination frequencies do not change with age in male mice (Polani and Jagiello, 1976;Jagiello and Fang, 1979). Instead, a significant reduction in the mean number of MLH1 foci was found in 5-month-old heterozygous mice.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, determining the age of wild animals caught for investigations may be difficult. The effect of ageing on spermatogenic function has been addressed in laboratory mice with standard karyotype (Hacker-Klom, 1995;Wirth-Dzieciolowska and Czminska, 2000) and the absence of an age effect on recombination rates in mouse spermatocytes with standard karyotype was established long ago (Polani and Jagiello, 1976;Jagiello and Fang, 1979). Conversely, systematic investigation of the spermatogenic process in sexually mature wild-caught Rb mice and the possible variations with age is lacking.…”
Section: Copyright © 2003 S Karger Ag Baselmentioning
confidence: 99%
“…All the authors had been scoring gains or losses of whole chromosomes due to nondisjunction of chromosome pairs, but in 1991 an important study was published describing predivision in human oocytes at meiosis I (Angell, 1991). Precocious or premature centromere division of one homologue of a paired bivalent had been described in several organisms including two studies on mouse oocytes (Polani and Jagiello, 1976;Hansmann and El-Nahass, 1979) and the term predivison was used in the first of these studies. Essentially, the observations made are of single unpaired chromatids at metaphase II.…”
Section: Studies On Mature Oocytesmentioning
confidence: 99%
“…Thus, there is a decrease in chiasma frequency at diakinesis or metaphase I (3841), and an increase in univalents (3840). An increase with age in hyperploid metaphase II configurations has also been reported (42), but this may not continue past middle age (43), and since it may be absent altogether, some authors (40) have suggested that univalents at meiosis I are, for the most part, artifacts. The age effect on the spontaneous incidence of hyperdiploid Fi embryos is only on the borderline of significance or otherwise doubtful (23,44,45).…”
Section: Agementioning
confidence: 88%